Mysql Bible - Suehring, Steve (Wiley Publishing, 2011)
Organization: The book is divided into five parts: Getting Starated with MySQL and Relational Databases; Understanding SQL Through MySQL; MySQL Administration; MySQL Developer Guide; and Advanced and Specialized MySQL Topics. Comprehensive coverage: This Bible covers both beginning-level and advanced topics. Topics covered include: introduction to relational database management; installing and configuring MySQL on the Linux, Windows 2000, and Mac OS X operating systems; MySQL security; debugging and repairing MySQL databases and servers; MySQL performance tuning; and developing MySQL applications with Perl and PHP. Coverage of NuSphere MySQL: Due to the growing popularity of the NuSphere MySQL package, this book covers its enhancements and how to install and develop with NuSphere MySQL. Running database application: This book builds an e-commerce sample database application throughout to demonstrate concepts and topics.